2010
DOI: 10.1097/phm.0b013e3181d3e71f
|View full text |Cite
|
Sign up to set email alerts
|

Cycling Progressive Resistance Training for People with Multiple Sclerosis

Abstract: Specific exercise programs, including cycling progressive resistance training, may improve balance, fatigue, and depression and reduce fear of falling in patients with multiple sclerosis without worsening multiple sclerosis signs and symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
113
1
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(125 citation statements)
references
References 38 publications
5
113
1
6
Order By: Relevance
“…These findings link to other studies 23,[26][27][28] involving combined exercise interventions. Cakt et al 28 , found a significant improvement in fatigue scores following two months of resisted cycling and balance exercises in people with MS. With similar significant improvements in FSS results also being found by others 27 .…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…These findings link to other studies 23,[26][27][28] involving combined exercise interventions. Cakt et al 28 , found a significant improvement in fatigue scores following two months of resisted cycling and balance exercises in people with MS. With similar significant improvements in FSS results also being found by others 27 .…”
Section: Discussionsupporting
confidence: 60%
“…They found improvements in strength, fatigue and balance in both groups of subjects. Cakt et al 28 reported, from a randomised controlled trial, that two months of resisted cycling exercises followed by balance exercises twice weekly for around 60 minutes improved many assessed outcomes including participants" mobility, physical function and fatigue levels. Thus combined exercise programmes appear to offer an effective training option for those moderately affected with MS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, studies have demonstrated primary exercise benefits of improved balance and increased walking capacity, with secondary benefits of reduced fatigue, enhanced mood, improved QOL, and decreased perceived disability immediately following an 8-week strength-training program 3 and an aerobic exercise intervention. 4,5 Despite the demonstrated benefits, attrition in exercise intervention studies is a concern, ranging from just over 18% 6 to 42%.…”
mentioning
confidence: 99%